The Successfulness of the Reasons for Malaysia’s Energy Initiatives - Islam, Rabiul; Osman, Nazariah; Shuib, Md. Shukri; Dharfizi, Awang Dzul-Hashriq; Ghani, Ahmad Bashawir Abdul; Sultana, Sabina (International Journal of Energy Economics and Policy, 2023)
From the standpoint of Neoliberal Institutionalism, this study explores Malaysia’s participation in activities that make energy the topic and/or object of foreign policies, whether through bilateral or multilateral engagements. This research, which aims to evaluate the relevance of energy in Malaysia’s economy and diplomacy and to explain Malaysia’s reason for its involvement in these cooperations, is necessary because of Malaysia’s growing involvement in the global energy market. Information for this study was gathered from a variety of government sources, interviews, published statistical data, and previous studies. The study demonstrates how vital energy is to Malaysia’s economy. The Lao PDR-Thailand-Malaysia-Singapore Power Integration Project (LTMS-PIP) initiative, in which Malaysia is participating, is evidence of the viability of multilateral power commerce in the area. The Peninsula Gas Utilisation (PGU) pipeline in Peninsular Malaysia and the Four-Fuel Diversification Policy 1981 (4FDP 1981), which increases natural gas utilisation, are related to Malaysia’s participation in the Malaysia-Thailand Joint Development Area (MT-JDA). Malaysia would want to think about streamlining its energy administration.